Magnetic Relaxation Studies on Trigonal Bipyramidal Cobalt(II) Complexes. Issue 3 (16th January 2020) - Shao, Feng; Cahier, Benjamin; Wang, Yi‐Ting; Yang, Feng‐Lei; Rivière, Eric; Guillot, Régis; Guihéry, Nathalie; Tong, Jia‐Ping; Mallah, Talal
Abstract: We report the preparation and the full characterization of a novel mononuclear trigonal bipyramidal Co II complex [Co(NS3 i Pr )Br](BPh4 ) (1 ) with the tetradentate sulfur‐containing ligand NS3 i Pr (N(CH2 CH2 SCH(CH3 )2 )3 ). The comparison of its magnetic behaviour with those of two previously reported compounds [Co(NS3 i Pr )Cl](BPh4 ) (2 ) and [Co(NS3 t Bu )Br](ClO4 ) (3 ) (NS3 t Bu =N(CH2 CH2 SC(CH3 )3 )3 ) with similar structures shows that 1 displays a single‐molecule magnet behaviour with the longest magnetic relaxation time (0.051 s) at T= 1.8 K, which is almost thirty times larger than that of 3 (0.0019 s) and more than three times larger than that of 2 (0.015 s), though its effective energy barrier (26 cm −1 ) is smaller. Compound 1, which contains two crystallographically independent molecules, presents smaller rhombic parameters ( E= 1.45 and 0.59 cm −1 ) than 2 ( E= 2.05 and 1.02 cm −1 ) and 3 ( E= 2.00 and 0.80 cm −1 ) obtained from theoretical calculations. Compounds 2 and 3 have almost the same axial ( D ) and rhombic ( E ) parameter values, but present a large difference of their effective energy barrier and magnetic relaxation which may be attributed to the larger volume of BPh4 − than ClO4 − leading to larger diamagnetic dilution (weaker magnetic dipolar interaction) for 2 than for 3 . The combination of these factors leads to a much slower magnetic relaxation for 1 than for the two other compounds. Abstract : Under the counter : The counter anion together with subtle structural changes in the coordination sphere slow down the magnetic relaxation time in trigonal bipyramidal Co II complexes.